Análisis de la Planta Turística Oferta Agencias de Viajes de la Provincia de Cotopaxi - Zambonino Balarezo, Wendy Carolina (2019)
The main objective of this research is to analyze the tourist facility, offering travel agencies through the collection of information, in order to have an updated and characterized record of the existing establishments. For the execution of the project, a diagnosis of the current situation of the Cotopaxi province was carried out, through the collection of information in secondary sources, being the Plan of Development and Land Management of Cotopaxi, Ministry of Tourism and the National Institute of Statistics and Censuses the most important, because it allowed to know demographic, social, cultural data such as: its festivities, typical dishes, cultural and natural attractions that each canton has also detailed the economically active and the inactive population. An inventory was made of the establishments of travel agencies, in which a card was designed based on the tourism products contemplated in the PLANDETUR 2020, for the recognition of the existing and functioning establishments within each canton: where there is general data , type of agencies, infrastructure and equipment, products and services, through field research the information gathering was developed for each canton, since an on-site visit was carried out in which it was analyzed that there are 20 tourist establishments among International Agencies, operators and dual located in the three cantons that are: Latacunga, Salcedo and La Maná the same that offer various products and services, the Latacunga canton meets the necessary conditions for the arrival of several tourists that is why it has more travel agencies, being the operators those that have greater representativeness. A catalog was designed through the systematization of information in which the most relevant information of travel agencies is described by cantons with their most offered products and services. It consists of 15 pages with letters and visible images which serves as a source of information consultation associated with the tourist plant offer Travel agencies. This project recommends tracking the number of travel agency establishments since each year can increase or decrease the influx of both national and foreign visitors since some cases the agencies are closed.